1965
DOI: 10.1039/tf9656102013
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of amino-acids and peptides by montmorillonite and illite. Part 1.—Cation exchange and proton transfer

Abstract: Adsorption isotherms are presented for a range of naturally occurring neutral and acid aminoacids on hydrogen montmorillonite and of basic amino-acid and peptide cations on sodium and calcium montmorillonite and illite. Differences in the isotherms show that the electrostatic bonding which results from proton transfer and cation exchange respectively is supplemented by physical adsorption forces. The magnitude of the physical adsorption forces is determined by the molecular weight and by the shape of the adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…Adsorption was ascribed mainly to cation-exchange reactions, but with a significant contribution also from hydrophobic interactions. X-ray diffraction data [11] suggested that acidic and neutral amino acids can intercalate into the interlayer spaces of montmorillonite.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adsorption was ascribed mainly to cation-exchange reactions, but with a significant contribution also from hydrophobic interactions. X-ray diffraction data [11] suggested that acidic and neutral amino acids can intercalate into the interlayer spaces of montmorillonite.…”
Section: Introductionmentioning
confidence: 98%
“…In previous studies of clay systems the sorption of a range of amino acids from salt-free aqueous solutions [7,11] or from seawater [8] to kaolinite [7,8], montmorillonite [7,8,11], or illite [11] was measured at discrete pH values, depending on the particular amino acid solutions and clay suspensions under study. The effect on sorption of varying the pH was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Effective antimicrobial coatings on textile substrates with such clay materials can be achieved by using a mixture of the precursors glycidoxypropyltriethoxysilane and tetraethylorthosilicate. After complete hydrolysis of the silane precursors, the exchanged clay material (mixture of illite and calcite) can be Hang and Brindley (1970) 1.87 13.9 95 Greenland et al (1965) 29.3 88 Busenberg and Clemency (1973) 3 added to the sol to yield the final coating agent, which can be applied by a pad-drycure process. It should be noted that the maximum clay concentration in the sol-gel coating agent is limited.…”
Section: Coatings and Applications With Biological Components Sol-gelmentioning
confidence: 99%
“…It is noteworthy to mention that van der Waals forces are also involved in the adsorption of organic cations. The importance of the shape of the cations in determining the extent of van der Waals interaction has been demonstrated by Greenland et al (1965) on the adsorption of some amino acids and peptides by montmorillonite. Since van der Waals forces are known to decay rapidly with distance, their contribution to the adsorption energy would be greatest for those ions which are in closest contact with the surface, or enable close contact to be maintained with the adjacent adsorbed ions.…”
Section: Adsorption Mechanismsmentioning
confidence: 98%